Body Mass Index (BMI) dengan Preeklampsia pada Ibu Hamil Trimester III - Sulis Diana; Fitria Edni Wari; Farida Yuliani; Erfiani Mail (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2022)
Preeclampsia if not treated properly, can lead to the death of the mother and baby. The cause of preeclampsia is unknown, women with a high BMI (Body Mass Index) or obesity before pregnancy are at greater risk for developing preeclampsia. This study is an observational analytic study with a case control approach with a retrospective approach. The purpose of this study was to determine the relationship between BMI and preeclampsia. The sample of this study was divided into case groups, namely third trimester pregnant women with preeclampsia and control group samples; namely third trimester pregnant women who did not experience preeclampsia. The number of samples in each group was 14 respondents. Data analysis using Chi Square statistical test. The results showed that most (19 respondents) pregnant women with TM III (67.9%) with abnormal BMI experienced preeclampsia as many as 13 respondents (46.4%). Meanwhile, of the 9 respondents of TM III pregnant women with normal BMI, most of them did not experience preeclampsia, namely 8 respondents (28.6%). Chi Square test results obtained p - value = 0.005 (< 0.05) which indicates there is a relationship between BMI and preeclampsia. More pregnancy monitoring in pregnant women with obesity and overweight categories is needed to avoid the occurrence of preeclampsia.